Potrzeba budowy teorii dydaktycznych jako wymóg rozwoju dydaktyki ogólnej - Piotrowski, Eugeniusz (Kultura-Społeczeństwo-Edukacja, 2018)
This paper’s concern is the need to construct didactic theories in the aspect of the development of general didactics. The author performs an analysis of the various ways the term ‘theory’ is understood in the many field of scientific inquiry. What follows is a discussion of the problems of scientific cognition, researcher’s methodological awareness, as well as the models of pedagogy: the scientist, hermeneutic and praxeological models. Finally, the author draws attention to the sources of researcher’s expectations, axiological dilemmas in pedagogical research and potential conflicts of values.